2009
DOI: 10.1007/s12355-009-0065-x
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of sugarcane smut (Sporisorium scitamineum) through botanicals and Trichoderma viride

Abstract: Culmicolus smut (Sporisorium scitamineum Meike), the sett borne pathogen causes considerable loss to sugarcane productivity especially to ratoon crop. Use of fungicides may cause environmental hazards besides residual problem. Therefore, twenty five plant species and Trichoderma viride was evaluated in vitro against smut pathogen (Sporisorium scitamineum). Out of twenty five plant species, leaf extracts (10%) of Calendula officinalis, Solanum nigrum and culture filtrate (5%) T. viride (bioagent) inhibited myce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…This method has been widely used to control the plant diseases caused by Fusarium and Verticillium species (Matta and Garibaldi, 1977;Larkin and Fravel, 1998;Nel et al, 2006;Zhu et al, 2013). The efficiency of a particular BCA against plant diseases can be altered by many factors such as; environmental factors, time of treatment, season of the application, nature or technique of the treatment and the frequency of the application (McLaughlin et al, 1990;Wu and Hsiang, 1998;Ali-Shtayeh and Saleh, 1999;Schisler et al, 2002;Bhagat and Pan, 2007;Lal et al, 2009;Perellóet al, 2009;Padder and Sharma, 2011). The same BCA Benhamou et al, 1997;Gerbore et al, 2014 Seed rot of tomato Globisporangium ultimum (Pythium ultimum) He et al, 1992;Gerbore et al, 2014 Pythium damping-off in cress and sugar-beet…”
Section: Discussionmentioning
confidence: 99%
“…This method has been widely used to control the plant diseases caused by Fusarium and Verticillium species (Matta and Garibaldi, 1977;Larkin and Fravel, 1998;Nel et al, 2006;Zhu et al, 2013). The efficiency of a particular BCA against plant diseases can be altered by many factors such as; environmental factors, time of treatment, season of the application, nature or technique of the treatment and the frequency of the application (McLaughlin et al, 1990;Wu and Hsiang, 1998;Ali-Shtayeh and Saleh, 1999;Schisler et al, 2002;Bhagat and Pan, 2007;Lal et al, 2009;Perellóet al, 2009;Padder and Sharma, 2011). The same BCA Benhamou et al, 1997;Gerbore et al, 2014 Seed rot of tomato Globisporangium ultimum (Pythium ultimum) He et al, 1992;Gerbore et al, 2014 Pythium damping-off in cress and sugar-beet…”
Section: Discussionmentioning
confidence: 99%
“…Que et al (2014) juga menyatakan kerugian hasil akibat penyakit luka api sangat bervariasi, tergantung ketahanan tanaman terhadap patogennya, dengan kehilangan hasil mulai dari 30% hingga tidak dapat dipanen. Kehilangan hasil pada tanaman ratun lebih tinggi dibandingkan dengan plant cane (PC) (Lal et al, 2009).…”
Section: Stoll and Oberw (Sebelumnya Bernamaunclassified
“…Adapun pengendalian secara kuratif dapat dilakukan dengan eradikasi tanaman yang terinfeksi dengan mencabut seluruh batang dalam satu rumpun meskipun hanya ada satu batang yang bergejala untuk mencegah menyebarnya spora di lapangan (Wada et al 1999;Bhuiyan et al 2013;Shailbala et al 2013). Lal et al (2009) (Bhuiyan et al, 2012;Rajput et al, 2019). Aplikasi fungisida ini dimaksudkan untuk mengurangi sumber inokulum awal dan menurunkan laju perkembangan penyakit (Putra & Damayanti, 2012).…”
Section: Strategi Pengendalian Penyakit Luka Apiunclassified
“…Malathi et al [68] confirmed the detoxification of phytotoxin produced by the sugarcane red-rot pathogen C. falcatum Went by antagonistic T. harzianum strains. Lal et al [59] reported the inhibition of mycelia growth and teliospore germination of Sporisorium scitamineum when sugarcane setts were treated with culture filtrate of T. viride and leaf extract of Solanum nigrum and Calendula officinalis before transplantation. Sett treatments with culture filtrate of T. viride improved germination, millable canes (27%) and cane yield (38%) in plant crop and sprouting of clumps, millable canes (51%) and yield (49%) in ratoon crop.…”
Section: Fungimentioning
confidence: 99%